al-Ḍiffah al-Gharbīyah = The West Bank : publications (Filmed by the University of Chicago Library Photoduplication Laboratory for the Middle Eastern Microfilm Project at the Center for Research Libraries, 1993)
Collection of 13 documents in Arabic and English on the political situation in the West Bank, published by various organizations from 1965-1991; filmed from originals held by the Library of Congress.